Introduction to RF stealth - Lynch, David (David D.) (SciTech Publishing, 2004)
The book reviews developments in the following fields: stealth systems; interceptability parameters and analysis; intercept receivers; stealth waveforms; stealth antennas and radomes; and signal processing.